Contribution Agreement between the State of the Natherlands and BRAC (2009) - The State of the Netherlands; BRAC (The State of the Netherland and BRAC, 2013)
The State of the Netherlands, represented by the Minister for Development Cooperation, legally represented in this matter by Mrs. Bea ten Tusscher, Head of Mission of the Embassy of the Kingdom of the Netherlands in Bangladesh, hereafter referred to as the Minister, on the one hand and BRAC, established and with offices in Dhaka 1212, 75 Mohakhali, Bangladesh, legally represented in this matter by Mr. Fazle Hasan Abed, Chairperson, hereafter referred to as the other party, on the other hand, Considering that the Minister is prepared to make a contribution to the other party for the activity "Education Research, Training and Advocacy (ERTA)" to be implemented by the other party through the Institute of Educational Development (IED) of BRAC University (BU), as described in the letter dated 4 December 2008 (Appendix 1), including the revised-program proposal dated November 2008, (Pir 1841 and contract number DHA 0109691)